The Effect of Artificial Intelligence Integration and Computational Thinking on Students’ Religious Problem-Solving Ability in Islamic Religious Education Learning - Khairrina (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The rapid adoption of Artificial Intelligence (AI) has transformed educational practices worldwide, yet its pedagogical value in value-based learning remains insufficiently understood. Previous studies have largely examined AI and computational thinking in STEM, higher education, and general digital learning contexts, leaving Islamic Religious Education underexplored. This study investigates the effects of AI integration and computational thinking on students’ religious problem-solving ability in Islamic Religious Education learning. Using a quantitative explanatory correlational survey design, data were collected from 150 grade XI senior high school and madrasah students selected through purposive sampling. A five-point Likert-scale questionnaire was used to measure AI integration, computational thinking, and religious problem-solving ability. The data were analyzed using descriptive statistics, validity and reliability testing, classical assumption tests, Pearson correlation, and multiple linear regression with IBM SPSS Statistics. The findings show that AI integration had a positive and significant effect on religious problem-solving ability. Computational thinking also had a positive and significant effect and emerged as the stronger predictor. Simultaneously, AI integration and computational thinking explained 57.5% of the variance in students’ religious problem-solving ability. These findings indicate that the educational value of AI in Islamic Religious Education depends not only on technological access, but also on students’ ability to process information systematically, ethically, and contextually. This study extends technology-enhanced learning and computational thinking literature by positioning computational thinking as a cognitive mechanism that transforms AI-supported information into value-based religious problem solving. Practically, the findings highlight the need for AI-supported Islamic Religious Education that integrates source verification, guided questioning, ethical reflection, and structured reasoning.